PENGARUH WEBSITE INTERFACE FEATURES, BRAND AMBASSADOR DAN CREATIVE ADVERTISING TERHADAP ADVERTISING EFFECTIVENESS SERTA DAMPAKNYA TERHADAP ONLINE SHOPPING INTENTION - Wibowo, Bambang Setia (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2016)
This study examined the influence of brand ambassador reputation, websiteinterface features and creative advertising to advertising effectiveness and its impact toonline shopping intention. This study is the integration of previous studies to determinethe effect of simultaneous between variables and the variable advertising effectiveness asa mediating variable in the influence of brand ambassador reputation, website interfacefeatures and creative advertising to online shopping intention. Respondents of this studywere 115 university students who have ever seen e-commerce advertisements on electronicmedia participated in this reseach. There are several findings in this study. First, brandambassador reputation has positive effect to advertising effectiveness. Second, website interface features has positive influence to the advertising effectiveness. Third, creativeadvertising has positive effect to advertising effectiveness. Fourth, advertising effectivenesshas positive effect on online shopping intention. Fifth, advertising effectiveness perfectlymediate the effect of brand ambassador reputation, website interface features and creativeadvertising to the online shopping intention.Keywords : brand ambassador reputation, website interface features, creative advertising,advertising effectiveness, online shopping intention